SIGNAL AS A TOOL OF THE PHARMACOVIGILANCE - E. O. Zhuravleva; N. Yu. Velts; G. V. Kutekhova; M. A. Darmostukova; R. N. Alyautdin (Безопасность и риск фармакотерапии)
The European Medical Agency (EMA) in 2012 formulated modern legislation defining the procedure for pharmacovigilance — the Good Pharmacovigilance Practices (GVP), which replaced the earlier provisions of the Pharmacovigilance Guidelines for Human Medicines. The signal management position is included in one of the GVP EMA modules and became part of the EAEC GVP Rules. EMA in 2017 published a regulatory guide for detecting a signal in spontaneous reporting databases, which became an Annex to Module IX of the GVP Rules «Signal Management». The approach proposed in the Appendix supplements the classical analysis of disproportionality with other data, based on both statistical and clinical judgments. The article deals with the problem of detecting signals about the safety of medicines. The main parameters that determine the effectiveness of methods for detecting signals on disproportionality and allowing to compare the productivity of different statistical methods with respect to each other are considered. Priority directions are considered when evaluating the signal, and key elements of a qualitative method for detecting signals are drawn up, taking into account the expert opinion.